A comparison of list vs. hierarchical UIs on mobile phones for non-literate users - Medhi, Indrani; Toyama, Kentaro; Joshi, Anirudha; Athavankar, Uday; Cutrell, Ed; Thies, Indrani Medhi (Interact: 14th IFIP TC13 Conference on Human-Computer Interaction, 2013)
Previous research has shown that low-literate users have difficulty using hierarchical information architectures and that a list design showing all items at once on a PC screen works best for search tasks. However, the limited screen space on phones makes it impossible to show more than a few items at once on a single screen. Does a hierarchical UI work better on a phone? In this study, we compared the performance of non-literate users from Bangalore, India, on a search task using a hierarchical UI (four levels deep) and a multi-page list that had forty items across seven pages of a touch-screen phone. Our results show that participants using the multi-page list perform better both in terms of time taken and percent correct even when the list UI design requires them to browse through multiple pages of items on the phone.